A8.11 Th17 cells as a diagnostic biomarker for rheumatoid arthritis (RA): Pilot data using an epigenetic QPCR assay. (24th February 2016) - Ponchel, F; Burska, AN; Raschke, E; Olek, S; Emery, P
Abstract : Background: A considerable interest has risen about the interplay between immune suppression and polarisation particularly with Th17 cells. Although Th2 polarisation seems intact in rheumatoid arthritis (RA), Th1 has long been known to be perturbed with lack of appropriate epigenetic commitment. Defective polarisation could be a mechanism by which Th1/Th17 cells preferentially develop. There are conflicting results about Th17 cell frequency in the blood of RA patients due to different phenotypes being used to define Th17 by flow-cytometry. Here, we investigated whether a novel epigenetic assay for Th17 cell frequency quantification could be used to differentiate patients with early RA from patients with early inflammatory arthritis symptoms evolving towards an alternative diagnosis. Materials and methods: We used an epigenetic Th17 qPCR assay that quantifies Th17 cells based on a cell-specific methylation pattern at a key position in the IL-17 gene/promoter (Th17 qPCR; http://www.epiontis.com/immune-monitoring/available-assays/ ). CD4+ T-cell frequencies were measured using the same epigenetic assay format based on a CD4+ T-cell-specific biomarker and results were used to normalise Th17 frequency to CD4+ T-cells. The Th17/CD4+ T-cell epigenetic assays were performed in whole blood extracted from healthy controls (HC, n=45), stable undifferentiated arthritis (UA) over 12–24 months (n = 43), UA patients progressing to RA (n = 22) and newly diagnosed RA patients (n = 45), other inflammatory arthritis (n = 30) and non-persisting symptoms (n = 16), as well as palindromic arthritis (n = 15). Results: There was no difference between groups for the frequencies of CD4+ T-cells. Data suggest that Th17/CD4+ T-cells are significantly less frequent in the blood of early, DMARDs naïve RA patients compared to HC (p < 0.0001) and patients with long lasting UA (p < 0.0001). While HC and UA are not different (p = 0.513), patients starting with UA and progressing to RA (within 6–12 months) are different from both HC (p < 0.00001) and stable UA (p = 0.001), but not from RA (p = 0.475). This finding can be explained by Th17 cell recruitment to the inflammatory disease site from the circulation as recently reported 1, 2, 3 thus resulting in lower Th17/CD4+ T-cell frequencies in the blood. A power calculation based on these results suggested the need to test a further 30 patients from an early arthritis clinic evolving towards alternative diagnoses (AS, PsA, gout, reactive), and 16 patients with non-persistent symptoms. 15 patients with palindromic arthritis were also included. The measurement showed that Th17 frequencies in RA and other forms of inflammatory arthritis are less significantly different (p = 0.01), although frequencies between RA and non-inflammatory diseases are (p < 0.00001). Palindromic arthritis was not distinguishable from RA. Conclusions: While there are conflicting results with respect to Th17 cell frequency in blood, we demonstrated using an epigenetic qPCR assay that RA patients show robust differences in their blood Th17/CD4+ levels compared to the group comprising HC, UA or non-persistent diseases. There was less difference between RA and other forms of inflammatory arthritis including palindromic arthritis. Our results suggest that together with Treg, Th17 may leave the blood in early RA and be recruited to the site of inflammation. A certain degree of interplay and plasticity between Treg/Th17 cells may explain why Treg are not capable of suppressing responses at the disease site if Th17 are also present. References: Chalan P, et al . PLoS One; 2013;8(11):e79370 Arroyo-Villa I, et al . PLoS One; 2012;7(8):e42189 Hirota K, et al . J Ex Med; 2007;204(12):2803–2812